2007
DOI: 10.1007/s10340-007-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of entomopathogenic fungi to Thaumetopoea pityocampa (Schiff.) (Lepidoptera: Thaumatopoeidae) larvae in laboratory conditions

Abstract: Pathogenicity of 13 strains of entomopathogenic fungi belonging to genera Paecilomyces, Tolypocladium, Beauveria, Metarhizium, and Lecanicillium (=Verticillium) was evaluated on fourth instar larvae of Thaumetopoea pityocampa (Schiff.) (Lep.: Thaumatopoeidae). Larvae were treated individually by dipping into conidial suspension with the concentration of 1.0 · 10 5 conidia ml -1 . All the tested isolates resulted in various levels of mortality (16-100%), and eleven of them were able to grow and sporulate on dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 6 publications
2
17
0
2
Order By: Relevance
“…In the investigation of entomopathogenic fungi against Thaumetopoea pityocampa (Lepidoptera: Thaumatopoeidae) at concentrations of 1)10 5 conidia mL (1 , all isolates 1208 T.A. Goble et al tested resulted in various levels of mortality (16Á100%) and when doseÁmortality tests were undertaken by spraying five conidial concentrations on larvae, the estimated LC 50 value was 3.4 )10 6 conidia mL (1 (Er, Tunaz, and Gokçe 2007). Loc and Chi (2007) reported that B. bassiana, M. anisopliae and two commercially available biopesticides (Crymax † 35 WP and Atabron † 5EC) applied at concentrations of 1 )10 7 conidia mL (1 were able to induce 70Á87.3% mortality in, P. xylostella, larvae 7 days after exposure when applied directly as sprays.…”
Section: Discussionmentioning
confidence: 99%
“…In the investigation of entomopathogenic fungi against Thaumetopoea pityocampa (Lepidoptera: Thaumatopoeidae) at concentrations of 1)10 5 conidia mL (1 , all isolates 1208 T.A. Goble et al tested resulted in various levels of mortality (16Á100%) and when doseÁmortality tests were undertaken by spraying five conidial concentrations on larvae, the estimated LC 50 value was 3.4 )10 6 conidia mL (1 (Er, Tunaz, and Gokçe 2007). Loc and Chi (2007) reported that B. bassiana, M. anisopliae and two commercially available biopesticides (Crymax † 35 WP and Atabron † 5EC) applied at concentrations of 1 )10 7 conidia mL (1 were able to induce 70Á87.3% mortality in, P. xylostella, larvae 7 days after exposure when applied directly as sprays.…”
Section: Discussionmentioning
confidence: 99%
“…We justified the choice of spore types tested based on what is currently available or being pursued for commercial application. We chose to test only conidia of B. bassiana and M. anisopliae because conidia are used in the current commercial products and we chose to test both blastospores and conidia for I. fumosorosea because active research is currently underway for use of both spore types (Dunlap et al, 2007;Er et al, 2007;Yanagawa et al, 2008). Additionally, we justified our approach and comparisons because we produced the fungal spores using standard methods for each spore type and fungal species in a manner similar to spore type comparisons made in other studies (Behle et al, 2006;Vandenberg et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, these insect pathogens have been evaluated as biological control agents but only B. thuringiensis is actively in use (Battisti et al 1998;Demolin et al 1993;Er et al 2007). Application of preparations of the bacterium Bacillus thuringiensis HD-1 subsp.…”
Section: Introductionmentioning
confidence: 98%